(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As global capital flows expanded manifold and into different sectors, India’s approach towards FDI too changed ever since independence, the initial approach overwhelmingly reflecting hostility following the experience with the colonial rule. From being assigned the role of supplementing and strengthening the domestic private sector, FDI was given greater freedom and a role of its own to contribute to India’s development process along with gradual liberalization of India’s economic policies which started in the 1980s.130 The New Industrial Policy, 1991, accelerated the process of liberalization, while Government would continue to follow the policy of self-reliance, there would be greater emphasis placed on building up our ability to pay for imports through own foreign exchange earnings. The government was welcome foreign investment which was in the interest of the country’s industrial development